1997
DOI: 10.1073/pnas.94.12.6279
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro tubulogenesis system using cell lines derived from the embryonic kidney shows dependence on multiple soluble growth factors

Abstract: Interactions between the ureteric bud (UB) and metanephric mesenchyme are crucial for tubulogenesis during kidney development. Two immortalized cell lines derived from the day 11.5 embryonic kidney, UB cells, which appear to be epithelial (cytokeratin-positive, E-cadherinpositive, and ZO-1-positive by immunostaining) and BSN cells, which are largely mesenchymal (vimentin-positive, but negative for cytokeratin, cell surface E-cadherin, and cell surface ZO-1), were used to establish an in vitro tubulogenesis sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 37 publications
4
127
0
1
Order By: Relevance
“…Of note, it has been shown that the UB cell line can form tubules under conditions somewhat similar to those we have shown as optimal for branching of the isolated UB (48). It has also been shown that adult ''progenitorlike'' cells from the injured mouse kidney can form tubular epithelial structures in vitro and migrate to multiple compartments of the developing kidney in organ culture (14).…”
Section: Discussionmentioning
confidence: 75%
“…Of note, it has been shown that the UB cell line can form tubules under conditions somewhat similar to those we have shown as optimal for branching of the isolated UB (48). It has also been shown that adult ''progenitorlike'' cells from the injured mouse kidney can form tubular epithelial structures in vitro and migrate to multiple compartments of the developing kidney in organ culture (14).…”
Section: Discussionmentioning
confidence: 75%
“…The Met receptor is expressed by metanephric mesenchyme as well as by the epithelium of the ureteric bud and later by S-shaped bodies and tubules. Neutralizing antibodies against HGF blocked branching morphogenesis by the ureteric bud in organ cultures of kidney rudiments and inhibited the early steps in branching morphogenesis by immortalized ureteric bud cells (UB cells) in threedimensional organ culture (7,8). Antibodies against HGF, in addition to their effects on branching morphogenesis, inhibited glomerulogenesis and nephrogenesis.…”
mentioning
confidence: 99%
“…6,7,12 Nigam and coworkers utilized isolated rat metanephros organ cultures and explants of isolated UBs to show that multiple growth factors including FGFs support UB growth and branching in vitro. 16,17 Qiao et al (this group) showed that addition of soluble FGF receptors or of FGF blocking antibodies to organ cultures inhibits UB branching. 16 Several FGFs including FGF2 in combination with GDNF and BSN-CM regulated isolated UB growth and branching in vitro.…”
Section: Resultsmentioning
confidence: 99%